2020
DOI: 10.1101/2020.06.26.173724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale association analyses identify host factors influencing human gut microbiome composition

Abstract: AbstractTo study the effect of host genetics on gut microbiome composition, the MiBioGen consortium curated and analyzed whole-genome genotypes and 16S fecal microbiome data from 18,473 individuals (25 cohorts). Microbial composition showed high variability across cohorts: we detected only 9 out of 410 genera in more than 95% of the samples. A genome-wide association study (GWAS) of host genetic variation in relation to microbial taxa identified 30 loci affecting microbome taxa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 90 publications
2
31
1
Order By: Relevance
“…These results recapitulate recent evidence for an mbQTL effect of this locus on the Collinsella genus and on other bacteria reported for a Finnish population cohort 18 . Associations of a functional variant in the FUT2 gene to other bacterial taxa were observed in a recent meta-analysis, but none of these bacterial taxa or pathways showed significant association for this locus in our cohort 13 .…”
Section: Introductionsupporting
confidence: 45%
See 2 more Smart Citations
“…These results recapitulate recent evidence for an mbQTL effect of this locus on the Collinsella genus and on other bacteria reported for a Finnish population cohort 18 . Associations of a functional variant in the FUT2 gene to other bacterial taxa were observed in a recent meta-analysis, but none of these bacterial taxa or pathways showed significant association for this locus in our cohort 13 .…”
Section: Introductionsupporting
confidence: 45%
“…However, reproducibility of these findings has been limited by differences in data processing methodologies, modest sample sizes and strong environmental effects, which, taken together, limit the detection of robust host genetic associations 12 . A recent large-scale genomewide meta-analysis of 24 cohorts replicated the association between Bifidobacterium abundance and the lactase (LCT) gene locus 13 , which had previously only been reported in single-cohort studies 6,14 . Other suggestive mbQTLs identified in this broad meta-analysis were proportional to heritability estimates from independent twin studies, indicating that additional loci found at lenient levels of significance are likely to be real but that larger sample sizes are needed to reach sufficient statistical power 13 .…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…While genus Methanobrevibacter has been consistently found to have a moderate heritability the TwinsUK (19,46,66) and other cohorts (48,67), it was not the case for members of Methanomassiliicoccales. Similar to humans, methane production (68) and abundance of Methanobrevibacter (69) are also heritable in bovine cattle, but not Methanomassiliicoccales taxa (69).…”
Section: Discussionmentioning
confidence: 89%
“…While genus Methanobrevibacter has been consistently found to have a moderate heritability the TwinsUK (19,46,66) and other cohorts (48,67), it was not the case for members of Methanomassiliicoccales. Similar to humans, methane production (68) and abundance of Methanobrevibacter (69) are also heritable in bovine cattle, but not Methanomassiliicoccales taxa (69).…”
Section: Discussionmentioning
confidence: 94%